2016
DOI: 10.1016/j.eucr.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyosarcoma Presenting as a Scrotal Mass

Abstract: Scrotal leiomyosarcoma is a rare tumor arising from the dartos layer of the scrotum presenting as firm, rubbery, non-tender, irregular mass. To date about 37 cases of leiomyosarcoma of scrotum have so far been reported. Treatment involves wide surgical excision with tumor free margins. We report a case of scrotal leiomyosarcoma in a 48-year-old man which was treated by a wide surgical excision and follow up of 14 months showed no recurrence of tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The data for adjuvant therapy is limited, though adjuvant radiotherapy has been reported to reduce recurrences in some reports. [1,7] Our patient had a sub centimetric tumour. After discussion, we opted to follow up after surgery with adjuvant therapy.…”
Section: Discussion O F Ma N a G E Me N Tmentioning
confidence: 79%
“…The data for adjuvant therapy is limited, though adjuvant radiotherapy has been reported to reduce recurrences in some reports. [1,7] Our patient had a sub centimetric tumour. After discussion, we opted to follow up after surgery with adjuvant therapy.…”
Section: Discussion O F Ma N a G E Me N Tmentioning
confidence: 79%
“…Adjuvant radiotherapy should be considered when resection with negative margins is not possible. If the possibility of incomplete tumor resection is foreseen, there is a superior oncological benefit from the use of neoadjuvant radiotherapy but with a higher rate of surgical complications and local healing [12,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…The role of RPLND in the management of scrotal and paratesticular soft tissue sarcomas is considered controversial [ 16 ]. Catton et al reported that patients presenting with primary disease had a regional recurrence rate of 28% suggesting that patients with rhabdomyosarcoma, fibrous histiocytoma, or fibrosarcoma may require RPLND [ 17 ].…”
Section: Discussionmentioning
confidence: 99%